The Black body in ecstasy: reading race, reading pornography - Nash, Jennifer C. (Duke University Press, 2014)
In The Black Body in Ecstasy, Jennifer C. Nash rewrites black feminism's theory of representation. Her analysis moves beyond black feminism's preoccupation with injury and recovery to consider how racial fictions can create a space of agency and even pleasure for black female subjects. Nash's innovative readings of hardcore pornographic films from the 1970s and 1980s develop a new method of analyzing racialized pornography that focuses on black women's pleasures in blackness: delights in toying with and subverting blackness, moments of racialized excitement, deliberate enactments of hyperbolic blackness, and humorous performances of blackness that poke fun at the fantastical project of race. Drawing on feminist and queer theory, critical race theory, and media studies, Nash creates a new black feminist interpretative practice, one attentive to the messy contradictions—between delight and discomfort, between desire and degradation—at the heart of black pleasures.
Section: x, 219 p. : ill. ; 23 cm.
Keywords: 1900-1999; 1970-1979; 1980-1989; afro-féminisme; amériques; approches et analyses; cinéma; communication; corps; cours; discipline; féminisme afroaméricain; féminisme pop; lit4700; pornographie; premier cycle; périodes historiques; queer; régions géographiques; sexualité; thématiques; états-unis; études culturelles

Decoding Black Women: Policing Practices and Rape Prosecution on the Streets of Philadelphia - Irving, Toni (NWSA Journal, 2008)
Black women are generally displaced as victims of rape. The police response to the sexual assault of black women in general and lower-class black women in particular is illustrative of how sexual ideologies help construct complex social hierarchies that in turn structure rights. How the law currently deals with rape places black women outside of the narrative frames that legitimate entitlement. Rape continues to stand in for, and effectively obscure, other social, political, and economic concerns. Unpublished and often ignored, the rape narrative is a ripe site to supply oppositional interpretations of national experience and transmit some of the structural problems in the criminal justice system. Pulling from over two thousand “real” rape cases of low-income black women ignored and not investigated in Philadelphia between 1995 and 2000, this article reads black female rape narratives as case studies in order to discuss the way personal narratives of rape victims are structured by competing and overwhelming sociolegal narratives that undercut their reception. As the fastest growing prison population, the presence of the law to punish black women stands in stark contrast to the absence of the law to protect them.
Keywords: 1900-1999; 1990-1999; afro-féminisme; amériques; approches et analyses; arts; corps; cours; discipline; droit; droit des femmes* noires; droits des femmes*; féminisme afroaméricain; histoire et politique; intersectionnalité; inégalités; philadelphie; premier cycle; périodes historiques; racisme; ressource en ligne; régions géographiques; science politique; science politique et droit; sex2283; sexisme; systèmes d'oppressions; thématiques; viol; violences; états-unis; études littéraires

Le patriarcat ou le féminisme noir - Charlery, Hélène (Revue française d’études américaines, 2007)
Les travaux actuels parus sur le féminisme et la population noire aux États-Unis insistent fréquemment sur l’attitude des Africaines-Américaines à l’égard de l’idéologie féministe (Terrelonge ; Roth). Peu d’études en revanche ont été consacrées aux prises de position des hommes et des dirigeants noirs sur la question. D’après les analyses récentes, une majorité d’Africains-Américains, hommes et femmes, redouterait que le féminisme ne divise les genres au sein du groupe, qu’il n’écarte les Noirs de leur priorité dans la lutte contre la discrimination raciale ou encore qu’il n’engendre un débat médiatique sur la sexualité des Africains-Américains. À ces raisons, Pauline Terrelonge ajoute l’héritage du nationalisme noir de la seconde moitié des années 1960 (Terrelonge 563). On constate aussitôt que les prises de positions citées précédemment sont liées à l’histoire des Noirs aux États-Unis et de leur stigmatisation dans les discours dominants. Pour les Africains-Américains, le féminisme imposerait alors une confrontation entre la race et le genre, bien que les féministes noires aient toujours envisagé de prendre en compte « l’intersectionalité » des deux notions .
Keywords: 1900-1999; 1960-1969; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; afro-féminisme; amériques; approches et analyses; cours; discipline; féminisme afroaméricain; histoire et politique; intersectionnalité; masculinité; patriarcat; pol5185; premier cycle; périodes historiques; racisme; ressource en ligne; régions géographiques; sciences humaines; sexisme; sociologie; systèmes d'oppressions; thématiques; états-unis

Women of color and the reproductive rights movement - Nelson, Jennifer (New York University Press, 2003)
While most people believe that the movement to secure voluntary reproductive control for women centered solely on abortion rights, for many women abortion was not the only, or even primary, focus.Jennifer Nelson tells the story of the feminist struggle for legal abortion and reproductive rights in the 1960s, 1970s, and early 1980s through the particular contributions of women of color. She explores the relationship between second-wave feminists, who were concerned with a woman's right to choose, Black and Puerto Rican Nationalists, who were concerned that Black and Puerto Rican women have as many children as possible "for the revolution," and women of color themselves, who negotiated between them. Contrary to popular belief, Nelson shows that women of color were able to successfully remake the mainstream women's liberation and abortion rights movements by appropriating select aspects of Black Nationalist politics–including addressing sterilization abuse, access to affordable childcare and healthcare, and ways to raise children out of poverty–for feminist discourse.
Keywords: 1900-1999; 1960-1969; 1970-1979; 1980-1989; afro-féminisme; amériques; approches et analyses; discipline; femmes* de couleur; histoire; justice reproductive; militance; périodes historiques; régions géographiques; sciences humaines; sociologie; sofia; thématiques; états-unis